PYROXENES FROM THE EXTRUSIVE - EXPLOSIVE ROCKS OF THE UZON-GEIZERNAYA VOLCANO-TECTONIC DEPRESSION, EASTERN KAMCHATKA - Grib E.N. (My University, 1998)
The composition of pyroxene phenocrysts was examined in the volcanics (ranging from basalt to rhyodacite) of the Uzon-Geizernaya volcano-tectonic depression. Variations in the contents of certain components and in their ratios in the pyroxenes were analyzed as a function of the iron-number. Covariations of the concentrations of individual components in the pyroxenes were examined. The pyroxene produced during the pre-caldera state typically shows a tholeiitic trend in the rock sequence from basalt to rhyodacite: the iron number of the mineral increases with the decreasing temperature of the melt. The variations in the iron-number were controlled by the variation of volatiles in the upper crustal magma reservoir during the evolution of the melt. The highly and low ferrous pyroxene crystallized at low and high oxygen fugacity, respectively. A decrease in the temperature of the silicic melts at a high oxygen fugacity resulted in Ca redistribution between the coexisting pyroxenes. The Mn contents of the pyroxenes clearly correlate with the composition of the melt and oxygen fugacity. An inversion in the covariations of clinopyroxene components such as Si-Mg and Ca-Al from low silicic andesite to intermediate varieties to rhyodacite was possibly controlled by varying crystallization depths of the basic and silicic melts.